Implementation of Turbo Boyer Moore Algorithm for Hijab Online Shop Application - Zulaika Susanti; Nelly Astuti Hasibuan (The IJICS (International Journal of Informatics and Computer Science), 2021)
Hijab is an obligation for Muslim women to cover their genitals. Hijab itself is now not only used by adult women or casual people, but has also penetrated teenagers including female students. The development of online shops or commonly referred to as olshop through internet media has mushroomed in Indonesia, and is even well known by the general public. Today's smartphones have developed and are in great demand by the public because of the various features that appeal to the user community. The hijab buying and selling system using an Android-based mobile application is a hijab sale and purchase that can be done easily to provide accurate information to potential consumers, but due to the large number of hijab products being sold, it can make finding information on a hijab product desired by potential consumers difficult to obtain. quickly and precisely. To solve the above problems, the authors designed the hijab online shop application using one of the editors for android programming, namely, Eclipse Juno. The string matching algorithm is used to simplify the process of searching for information on a particular hijab product in the application designed by the author to apply the Moore Turbo Boyer algorithm